OBTENÇÃO E CARACTERIZAÇÃO DE CELULOSE MICROFIBRILADA DE CASCA DE SOJA E SEUS NANOCOMPÓSITOS COM POLIPROPILENO - Peres, Nayana Reggiani (2013)
The development of new materials takes into account factors such as need and sustentabilidade.Novas trends in modifying properties of polymeric materials have been observed due to increasing concern about the environment and the constant search by the use of fillers in polymeric materials. Among them, there are the lignocellulosic fibers, which in addition to reinforcing the polymer, are biodegradable low cost, low density and have no abrasive characteristic. The agro-industrial residues are a great source of raw materials, especially in the case of soybean hulls, which is a waste in abundance in our region ( Paraná ). However, it is not always possible to obtain the best features with the Shell Soy Gross ( CSB ) . Thus , in a first step we sought to obtain microfibrillated pulp from the CSB . Conducted to obtain microfibrillated pulp by grinding the colloid mill, proven by analysis of Zeta Potential . And then be obtained twin screw extruder via nanocomposites with the incorporation of 1, 3 and 5% of microfibrillated cellulose. Finally, the nanocomposites were characterized by analysis of tensile test scanning electron microscopy, atomic force microscopy, X-ray diffraction, rheological analysis, thermogravimetry, and mechanical impact tests. Through the zeta potential was proved that the dimensions were namometricas the SEM and AFM demonstrated good adhesion of the microfibrillated cellulose, XRD confirmed the crystallinity. According to rheological analysis showed an increase in molecular weight , with the incorporation of cellulose microfibrillated there was a slight increase in impact strength, and an increase in the stiffness of nanocomposites.